Find the remainder when x 2 0 2 5 is divided by ( x 2 + 1 ) ( x 2 + x + 1 ) ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
By remainder theorem , we have:
For a polynomial f ( x ) , the remainder of f ( x ) upon division by x − c is f ( c ) .
Let the remainder of x 2 0 2 5 upon division by ( x 2 + 1 ) ( x 2 + x + 1 ) be r ( x ) = x 3 + a x 2 + b x + c . We note that the roots of x 2 + 1 are ± i and those of x 2 + x + 1 is the cubic root of unity ω . Therefore we have:
r ( i ) i 3 + a i 2 + b i + c − i − a + b i + c = f ( i ) = i 2 0 2 5 = i
Equating the real and imaginary parts on both sides: { − a + c = 0 − 1 + b = 1 ⟹ a = c ⟹ b = 2 . We get the same results using − i instead of i .
And we have:
r ( ω ) ω 3 + a ω 2 + b ω + c 1 + a ω 2 + 2 ω + a a ω 2 + 2 ω + a ⟹ a = c = f ( ω ) = ω 2 0 2 5 = 1 = 0 = 2 Note that ω 3 = 1 and that ω 2 + ω + 1 = 0
Therefore r ( x ) = x 3 + 2 x 2 + 2 x + 2 .
Problem Loading...
Note Loading...
Set Loading...
Write x 2 0 2 5 = q ( x ) ( x 2 + 1 ) ( x 2 + x + 1 ) + r ( x ) , where r ( x ) is the remainder.
Substituting x = i gives i 2 0 2 5 = i = r ( i ) . From the options, only the third option satisfies r ( i ) = i .
For a rigorous solution, let r ( x ) = a x 3 + b x 2 + c x + d , and plug all the roots of ( x 2 + 1 ) ( x 2 + x + 1 ) one by one to get the equations and solve for the coefficients.